Pelatihan Keselamatan Konstruksi Bagi Pekerja Bangunan Gedung Di Desa Labuan Panimba Kabupaten Donggala: Pelatihan Keselamatan Konstruksi Bagi Pekerja - Muhtar, Tutang; Nirmalawati; Mastura Labombang; Moh Fatih Ghithrif; Ruchiyat Mubarak (Jurnal Pengabdian, 2024)
Construction safety in the workplace, especially in the construction services industry, needs full attention. Construction safety is all engineering activities to support construction work in realizing the fulfillment of safety, health and sustainability standards. Labuan Panimba Village is an area with a fairly large construction worker population. The implementation of the activity was carried out through briefing and simulation of the implementation of Personal Protective Equipment and Work Protective Equipment and knowing the various risks in carrying out construction work in the field for 30 participants. Based on the results of the training, the final target result is that construction workers will be able to practice well in the field related to construction safety